Factors associated with the implementation of COVID-19 health protocols among Indonesian older adults living in rural areas: A cross-sectional study - Nurul Maurida; Prestasianita Putri; Wike Rosalini (Jurnal Ners, 2022)
Introduction: Implementing health protocols became a challenge for older adults living in rural area. This study aimed to analyze the factors influencing implementation of COVID-19 health protocols among elderly in rural areas based on the Theory of Planned Behavior (TPB). Methods: This study used an explanatory survey with cross-sectional approach. The sample consisted of 100 older adults who resided in rural areas. Data were collected using the TPB questionnaire and COVID-19 health protocol questionnaire, both have 21 items. The data were analyzed using bivariate and multivariate analysis. Bivariate analysis used Pearson correlation, Chi-square test, and Fisher’s exact test. Multivariate analysis used multiple linear regression with a level of significance = 0.05. The independent variables were attitude toward behavior, subjective norm and perceived behavioral control while the dependent variable was the implementation of COVID-19 health protocols. Results: Gender (p < 0.001), age (p < 0.001), employment status (p < 0.001), attitude toward behavior (p < 0.001), subjective norm (p < 0.001) and perceived behavioral control (p < 0.001) were significantly associated with the implementation of COVID-19 health protocols, while education level (p = 1.000) was not significantly associated with  the implementation. The R-square shows 0.610 which indicates that TPB model can predict 61% of implementation of COVID-19 health protocols. Conclusions: The most dominant factor in increasing the implementation of the COVID-19 health protocol is attitude toward behavior. Nurse need to provide education to elderly and their family to increase the implementation of COVID-19 health protocols as prevention of transmission of COVID-19.